Knowledge Management in Public Research Institutions in Sri Lanka: As Perspective of the Research Officers - Endagamage, D. M; Dahanayake, C (International Journal of Advanced Science and Technology, 2020)
Knowledge Management is a systematic management of acquisition, retention, sharing and usage processes of explicit and implicit knowledge of individuals or organization. When reaching to the service excellence at any public sector research institution, Knowledge Management process generates competitive advantage. The present study examines whether the ‘Social Capital’ and ‘Information Technology Capability /Facilities’ have any significant impact on ‘Knowledge Management’ within public sector research institutions in Sri Lanka. This study has designed with the positivistic approach and done as a cross-sectional survey with self-administered questionnaire. Data collected from 150 research officers from four selected public research institutions and received 113 successful responses.The findings of the regression analysis show that the ‘Structural’ and ‘Relation’ dimensions of ‘Social Capital’, and the ‘Infrastructure’ and ‘Operations’ dimensions of Information Technology Capability/ Facilities, have significant impacts on the Knowledge Management with the model accuracy as 69.4%. The perception on Knowledge Management of the males is in higher level than their female counterparts. These results empirically confirmed that, any research institution could managesuccessfully and efficiently, the accrued knowledge of their researchers by facilitating these four areas.Further, it provides insight to managers to allocate organizational tangible assets and to improve theirorganizational effectiveness when deciding knowledge management practices.
Keywords: Explicate and Implicit Knowledge, Information Technology Capability, Knowledge Management, Social Capital